An integrated energy storage system coupling Ca(OH)2/CaO/CaCO3 thermochemical energy storage, supercritical CO2 cycle, and CO2 capture - Zhang, Yongqing; Liu, Huawei; Lu, Jia; Xu, Qianghui; Xu, Chao (Journal of energy storage, 2025)
Long-term energy storage and carbon dioxide capture technologies are essential for achieving the goal of ‘carbon neutrality’. This paper proposes a renewable electricity-driven Carnot battery system to realize long-term energy storage, residential heating, and carbon capture through effective energy conversion of electricity, thermal energy, and chemical energy. The Carnot battery system utilizes abundant and inexpensive calcium hydroxide as the feedstock for energy storage. When power demand is low, electricity-driven heat pump heats calcium hydroxide to produce water and calcium oxide, thus storing energy and supplying residential heat. During power consumption peaks, the generated calcium oxide is utilized to capture carbon dioxide and simultaneously drive a supercritical carbon dioxide Brayton cycle to generate electricity. Then, the produced calcium carbonate is stored and crushed during periods of low power demand to provide ground calcium carbonate. Using the differential evolution algorithm and the HEATSEP framework, a multi-level optimization workflow is established to optimize both the operating parameters and heat exchange network configurations. After optimizations, the heat exchange networks are also designed. The optimized Carnot battery system achieves an energy efficiency of 29.96 %, an exergy efficiency of 19.97 %, a round-trip efficiency of 28.03 %, and simultaneously provides a CO2 capture efficiency of 2.71 kg/kWh regenerated electricity. At the same time, an operating income of 0.557 $/kWh regenerated electricity is also achieved. •Carnot battery based on thermochemical energy storage is proposed.•Supercritical CO2 cycles and Ca(OH)2/CaO/CaCO3 reactions are integrated.•Industrial waste flue gas is utilized, and residential heat is provided.•The optimized system provides a CO2 capture efficiency of 2.71 kg/kWh.•An operating income of 0.557 $/kWh regenerated electricity is achieved.